Pengaruh Organizational Citizenship Behavior, Work Life Balance, dan Corporate Social Responsibility Terhadap Kepuasan Kerja pada Karyawan PT Pan Brothers Boyolali - Rania Salsabila; M. Farid Wajdi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the effect of Organizational Citizenship Behavior (OCB), Work Life Balance (WLB), and Corporate Social Responsibility (CSR) on employee job satisfaction at PT PAN Brothers Boyolali. The research method used is a descriptive quantitative approach with a sample of 63 employees from the warehouse material department. Data were collected through an online questionnaire using a 5-point Likert scale to measure the three independent variables and job satisfaction. Data analysis was performed using SmartPLS with the SEM-PLS method. The results indicate that OCB, WLB, and CSR have a significant positive effect on employee job satisfaction. OCB creates a harmonious work environment, WLB encourages employees to perform their roles more effectively, and CSR has a positive impact on job satisfaction. This study contributes to the development of human resource management strategies to improve job satisfaction through the OCB, WLB, and CSR approaches.